Test of the analysis of competing hypotheses in legal decision‐making. Issue 1 (1st September 2020) - Maegherman, Enide; Ask, Karl; Horselenberg, Robert; van Koppen, Peter J.
Summary: The analysis of competing hypotheses (ACH) has been suggested to be a method that can protect against confirmation bias in the context of intelligence analysis. In the current study, we aimed to determine whether ACH could counter confirmation bias in the reasoning with evidence in the context of criminal law proceedings. Law students ( N = 191) received information about the ACH method or general information about biases. They were given a case vignette with a main suspect and a list of 24 questions, 6 of which they could ask about the case. Half of the questions related to incriminating information, whereas the other half related to exonerating information. Contrary to our expectations, participants in both conditions favoured questions relating to exonerating information and rated the exonerating evidence as being more important for their decision. Despite the lack of bias observed, it seems participants failed to properly apply the ACH method.